Bangla sign language recognition using leap motion sensor - Tan, Tamkin Mahmud; Mondol, Anna Mary; Nawal, Noshin; Ahmed, Sabbir (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.